Features of fracture height propagation in cross-layer fracturing of shale oil reservoirs - Yizhao WANG; Bing HOU; Dong WANG; Zhenhua JIA (Petroleum Exploration and Development, 2021)
Triaxial fracturing modeling experiments were carried out on whole diameter shale cores from different layers of Shahejie Formation in the Dongpu sag, Bohai Bay Basin to find out the vertical propagation shapes of hydraulic fractures in different reservoirs. A numerical simulation method of inserting global cohesive elements was adopted to build a pseudo-three-dimension fracture propagation model for multiple shale oil reservoirs considering interface strength, perforation location, and pump rate to research the features of hydraulic fracture (HF) penetrating through layers. The hydraulic fracture propagates in a cross pattern in tight sandstone layers, in a straight line in sandstone layers with natural fractures, forms ladder fracture in shale layers with beddings. The hydraulic fracture propagates in a stripe shape vertically in both sandstone and shale layers, but it spreads in the plane in shale layers after connecting beddings. Restricted by beddings, the hydraulic fractures in shale layers are smaller in height than those in sandstone layers. When a sandstone layer and a shale layer are fractured at the same time, the fracture extends the most in height after the two layers are connected. Perforating at positions where the sandstone-shale interface is higher in strength and increasing the pumping rate can enhance the fracture height, thus achieving the goal of increasing the production by cross-layer fracturing in multiple shale oil layers.